2014
DOI: 10.22230/cjnser.2014v5n2a187
|View full text |Cite
|
Sign up to set email alerts
|

Individual and Organizational Factors in the Interchangeability of Paid Staff and Volunteers: Perspectives of Volunteers

Abstract: This study builds upon earlier studies of the degree of interchangeability between volunteers and paid staff in nonprofit organizations. While these earlier studies were from an organization perspective, this study is from the perspective of volunteers, and looks at individual and organizational characteristics in all types of organizations—nonprofits, for-profits, government agencies, and others. The findings indicate that 10.8% of volunteers reported replacing a paid staff member, 3.1% permanently. Volunteer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 12 publications
(23 reference statements)
0
7
0
Order By: Relevance
“…These circumstances lead to the appearance of process conflicts, defined as disagreements about how a task should be accomplished, including issues such as who should do what and how much responsibility each member of the group should take (Jehn, 1997;Jehn and Mannix, 2001). Indeed, Mook et al (2014) demonstrated that, on the one hand, 10.8% of volunteers reported that they replaced a paid staff member, with 3.1% of those cases permanently. On the other hand, volunteers also reported being replaced by paid staff: 7.6% reported being replaced, with 2.1% of those cases being permanently replaced.…”
Section: Conflicts Between Paid Staff and Volunteersmentioning
confidence: 99%
“…These circumstances lead to the appearance of process conflicts, defined as disagreements about how a task should be accomplished, including issues such as who should do what and how much responsibility each member of the group should take (Jehn, 1997;Jehn and Mannix, 2001). Indeed, Mook et al (2014) demonstrated that, on the one hand, 10.8% of volunteers reported that they replaced a paid staff member, with 3.1% of those cases permanently. On the other hand, volunteers also reported being replaced by paid staff: 7.6% reported being replaced, with 2.1% of those cases being permanently replaced.…”
Section: Conflicts Between Paid Staff and Volunteersmentioning
confidence: 99%
“…Such situations have been observed on several occasions (e.g. : Baines, 2004; Handy et al, 2008; Mook et al, 2014). In these cases, the increased use of volunteers is likely to go hand in hand with tighter wage restraint policies, which would in turn be reflected in lower wages than those paid by the non-profits not experiencing such economic difficulties.…”
Section: Theoretical Considerationsmentioning
confidence: 93%
“…It is also regularly mentioned in studies of the influence of organizational context on volunteering (Studer & von Schnurbein, 2013). And of course it is at the heart of research on the existence of complementarity or substitution between voluntary and paid work and their degree of interchangeability (Brudney & Gazley, 2002; Chum et al, 2013; Handy et al, 2008; Mook et al, 2014; Simmons & Emanuele, 2010; Stine, 2008).…”
Section: Introductionmentioning
confidence: 99%
“…Research has also shown that volunteers can experience tensions (e.g., competition and antagonism) as a result of interchangeability. Mook et al (2014), for instance, found that volunteers felt it was unfair when they were replaced by paid staff. However, they also felt it was unfair when they replaced paid staff.…”
Section: Nonprofit Paradoxmentioning
confidence: 99%